Characteristics of youth soccer players aged 13-15 years classified by skill level - Malina, R. M.; Ribeiro, B.; Aroso, J.; Cumming, S. P. (British Journal of Sports Medicine, 2007)
Objective: To evaluate the growth, maturity status and functional capacity of youth soccer players grouped by level of skill.